Involvement of The Manufacturing Industry In Supporting The Supply Chain ​​of NPP Development Program in Indonesia - Lela Elvira; Dharu Dewi; Rinfutihat; Dewi Astuti (The Eastasouth Management and Business, 2022)
The development of the industrial sector and the increasing number of people in Indonesia causes the use of energy to increase. Fossil energy which has been the main support for electricity generation in Indonesia has experienced limitations and is running low. The current strategic issue is the government's commitment to reduce greenhouse gas (GHG) emissions, namely reducing carbon emissions by 29% by 2030 with its own capabilities and 41% with international assistance. By 2060 it is expected to achieve the Net Zero Emission (NZE) target. Currently, most of the power generation still relies on fossil energy, which produces G. Nuclear energy is one of the clean energy options in the supply of electrical energy to meet the demand and need for electrical energy in Indonesia. The electrical energy produced by nuclear power plants is a very clean energy because it does not release carbon into the environment. However, nuclear energy among the general public is considered a dangerous energy based on the experience of the three largest nuclear accidents namely Chernobyl, Tree Mile Island and Fukushima. Nuclear energy is environmentally friendly energy and efficient in the use of resources. Government Regulation No. 79 of 2014 states that nuclear energy is included in new and renewable energy (EBT).